KALIGRAFI ASMAUL HUSNA DALAM SENI GRAFIS - Dwi Nurul Putri, Drs. Syafei, M.Ag., Yofita Sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose this final work is to visualize AsmaulHusna'scaligraphy in graphic art with stencil print technique. The method used there are five stages: preparation, elaboration, synthesis, concept realization and completion. At the end of the stages writer held exhibitions. Media used in the creating of graphic works art is watercolors on canvas. The 10 works include al-Malik, al-'Aziz, al-Mutakabir, al-Qahar, al-'Azhim, al-'Aliy, al-Kabir, al-Qawiy, al-Muqtadir, al-Baqiy representing themes who was raised about the greatness of God. If understanding the meaning of AsmaulHusna can feel the majesty of Allah SWT.Keywords: AsmaulHusna, graphics, stencil print